Electron–phonon coupling and superconductivity in a 2D Tl–Pb compound on Si(111). Issue 17 (14th April 2022) - Sklyadneva, I. Yu; Heid, R.; Echenique, P. M.; Chulkov, E. V.
Abstract : A first principles investigation of the electron–phonon interaction and phonon-mediated pairing strength in a Si(111) supported single-layer Tl–Pb compound reveals strong variations with electronic surface bands and binding energy. Abstract : Electron–phonon interaction in a single-layer Tl–Pb compound on Si(111) is investigated within the density-functional theory and linear-response approach in the mixed-basis pseudopotential representation. It is found that phonon-induced scattering of electrons at the Fermi level is primarily determined by surface electronic states responsible for bonding at the interface and by low-energy, predominantly shear-vertical vibrations of adatoms. The contribution of substrate-localized vibrations involved in the electron–phonon scattering turns out to be small. We have also estimated the superconducting transition temperature T c by solving the linearized gap equation of the Eliashberg theory. An analysis of phonon-mediated transitions for a number of electronic states in the Tl–Pb surface bands showed that the strength of the coupling varies with the binding energy, increasing as it approaches the Fermi level, and significantly depends on the surface band to which the state belongs.